Real estate brokerage and endowment effects in the housing market: Evidence from Poland - Tomal, Mateusz (International Journal of Strategic Property Management, 2024)
In the housing market, the prices sellers would be willing to accept to sell their properties exceed the prices buyers would be willing to pay for them. Behavioural economics postulates that this discrepancy is due to the endowment effect, which is a cognitive bias that causes the overvaluation of the goods we own. However, the existing literature lacks theoretical considerations and empirical evidence on the impact of the use of real estate agents by parties to transactions on the endowment effect in the housing market. Therefore, this study aims to assess the influence of real estate brokerage on the endowment effect using the example of the Polish residential market. To achieve the purpose of this study, a lab-in-the-field experiment was conducted with 248 respondents divided into sellers and buyers. The results indicate that the participation of real estate agents during transactions does not lead to the weakening or elimination of the endowment effect but, in some cases, to its intensification, which is due to the framing by buyers and sellers of the commission charged by agents as a loss requiring compensation. This research confirms the inefficiency of commission-based real estate brokerage services and points to possible corrective actions for legislators.